ANALISIS PENESRAPAN SISTEM MANAJEMEN KESELAMATAN KESEHATAN KERJA (SMK3) DI PERUSAHAAN - Dian Rahmah Mawarni Hasibuan; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
The occupational safety and health management system is part of the company's management system as a whole in order to control risks related to work activities to create a safe, efficient and productive workplace. Accidents at work also often occur in Indonesian industry. According to BPJS Employment data quoted from Data Indonesia, in 2020 there were 221,740 work accident cases, while in 2021 there were 234,270 work accident cases. The purpose of this literature is to find out the application of occupational safety and health management systems from various companies. The research method used is literature study by summarizing and analyzing secondary data according to the topic raised. In implementing SMK3 in the company, it must be applied to all employee members. However, not only employees, companies also lack knowledge about SMK3. In this literature, 8 out of 10 companies have implemented SMK3 in their companies and provided education to their workers about occupational safety and health. Lack of knowledge and education about SMK3 and work accidents will be potentially dangerous for workers